"This is nothing, fool": Shakespeare’s Vanities - Neill, Michael (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2020)
Remembering the Latin root of vanity in vanus meaning ‘empty’ or ‘void’, this essay explores the use of vanitas and memento mori motifs in early modern drama, and to the ways in which they are used to play upon primal fears of nullification. Paying particular attention to the relationship between vanity and folly, the essay concludes with an account of King Lear's Fool as a vanitas figure – a prophet of the terrifying nullity into which the tragedy descends. Keywords: Vanity, Emptiness, Nullification, Folly, King Lear